PEMODELAN STRUKTURAL DARI EMOSI POSITIF SEBAGAI PEMEDIASI TERHADAP PEMBELIAN TIDAK TERENCANA - YANITA, NI WAYAN ARNI; JAYANEGARA, KETUT; N. KENCANA, I PUTU EKA (E-Jurnal Matematika; Vol 4 No 3 (2015), 2015)
Latent variables are variables that can not be observed directly . Latent variables can be observed with constituent indicators. One of the methods used to analyze the latent variables are Structural Equation Modeling (SEM). This research raised the case of impulse buying to be applied to the SEM method. Impulse buying influenced by the characteristics of the hypermarket, situational factors, the characteristics of the product, promotion and positive emotions. The purpose of this research was to determine the effect dari positive emotions as mediation to impulse buying.The results obtained indicate that positive emotions directly affect the impulse buying of 0.302, promotion directly affects the positive emotions of 0.367, and the promotion of indirect effect to impulse buying of 0.111. So positive emotions can mediate to impulse buying of 0.020. Goodness of fit mediation models not good with value 0.39.
Keywords: Laten Variable; Structural Equation Modelling (SEM); Mediation; Impulse Buying